IMPROVEMENT OF FITTING AND MECHANICAL METHODS IN RESTORING THE OPERABILITY OF AXIAL-PISTON HYDRAULIC MACHINES OF HYDROSTATIC TRANSMISSIONS - Мельянцов, Петро (SWorldJournal, 2025)
The article addresses the problem of improving the repair quality of axial-piston hydraulic machines of hydrostatic transmissions through the enhancement of locksmith-mechanical methods. It is shown that traditional lapping and machining operations do no